The Oldowan of Zarqa Valley, Northern Jordan - Parenti, Fabio; Varejao, Filipe Giovanini; Scardia, Giancarlo [UNESP]; Okumura, Mercedes; Araujo, Astolfo; Guedes, Carlos Conforti Ferreira; Neves, Walter Alves (Springer, 2024)
The fluvial Dawqara Formation, upper Zarqa Valley, eastern side of Jordan Valley, is chronologically constrained between 2.52 and 1.98 Ma. Several artifact-bearing outcrops display a core and flake industry, with no handaxes nor planned flaking. Herein, we describe 40 artifacts from section 334 Lower, the earliest archeological site of the formation and one of the oldest Oldowan complexes outside Africa. Despite the occurrence of basalt rocks, all artifacts were made on chert cobbles displaying various degrees of abrasion due to fluvial transport. The industry is represented by 30 flakes and 10 cores and choppers, preferentially obtained on chert cobbles with massive-fan form, unifacially and bifacially flaked. Most of the flakes present plain or cortical platforms and show on their dorsal faces a unipolar production scheme. Eighteen flakes, from unipolar or undetermined cores, exhibit a discontinuous retouch, defining a denticulated or convex margin. The assemblage is compared to Oldowan or lower Acheulean complexes in and outside Africa, pointing to a rapid spread of unknown hominins with this flaking technology, possibly ascribable to an early Homo clade.
Keywords: Early Pleistocene; Oldowan; Taphonomy; Lithic technology; Zarqa Valley; Out of Africa